Sensors, measurement, intelligent materials and technologies III selected peer reviewed papers from the 2014 3rd International Conference on Sensors, Measurement and Intelligent Materials (ICSMIM 2014), November 25-26, 2014, Zhuhai, China - Kim, Yun-Hae; Yarlagadda, Prasad K. D. V. (Applied Mechanics and Materials, 2015)
Collection of selected, peer reviewed papers from the 2014 3 rd International Conference on Sensors, Measurement and Intelligent Materials (ICSMIM 2014), November 25-26, 2014, Zhuhai, China